Frontier Encounters : Knowledge and Practice at the Russian, Chinese and Mongolian Border - Grégory Delaplace
China and Russia are rising economic and political powers that share thousands of miles of border. Yet, despite their proximity, their interactions with each other, and with their third neighbour Mongolia, are rarely discussed. Although the three countries share a boundary, their traditions, languages and worldviews are remarkably different. Frontier Encounters presents a wide range of views on how the borders between these unique countries are enacted, produced, and crossed. It sheds light on global uncertainties: China's search for energy resources and the employment of its huge population, Russia's fear of Chinese migration, and the precarious independence of Mongolia as its neighbours negotiate to extract its plentiful resources. Bringing together anthropologists, sociologists and economists, this timely collection of essays offers new perspectives on an area that is currently of enormous economic, strategic and geo-political relevance.